The Nigerian Civil War of 1967-1970 and the Rwandan Civil War/Genocide of 1994: A Comparative Appraisal of Post-Civil War Peace Building in Nigeria and Rwanda - Eugene, Eugene O.; Akpe, Jeremiah Uko (NIU Journal of Social Sciences, 2022)
The end of colonialism brought about the emergence of independent African states. Since independence, a number of African states including Nigeria and Rwanda have experienced civil wars among other crises. While the Nigerian Civil War ensued and lasted from 1967 to 1970, the Rwandan Civil War cum Genocide was experienced in 1994; 24 years after the Nigerian Civil War. While these wars were fought and won on the perceived premise of ‘no victor, no vanquished’, the Federal Military Government of Nigeria and the Hutu ethnic group of Rwanda were the actual victors while the people of Eastern Nigeria then known as Biafra and the Tutsi of Rwanda were the vanquished. How these countries have fared in their post-civil war peace building processes have not been placed side by side. It is for this reason that a comparative appraisal of post-Civil War peace building in Nigeria and Rwanda after their civil wars becomes necessary. Nevertheless, years after these civil wars, Rwanda unlike Nigeria adopted workable efficient policies and strategies that enabled her to carry out an effective national reconciliation for overall national integration, growth and development of post-civil war Rwanda. To say the least, Rwanda has overcome the overall ills of the crises unlike in Nigeria, where the causes and factors that brought about the civil war are still very much present. The study is comparative and analytical and adopts both primary and secondary sources. It concludes therefore, that the Nigerian Government should study and adopt some of the policies and strategies adopted by Rwanda in ensuring efficient and effective post-civil war peace building which has placed Rwanda on the track of overall national development. Keywords: Civil War, Nigeria, Peace Building and Rwanda